Protection of diabetes in aortic abdominal aneurysm: Are antidiabetics the real effectors? - Picatoste, Belén; Cerro-Pardo, Isabel; Blanco-Colio, Luis M.; Martín-Ventura, Jose L. (Frontiers in Cardiovascular Medicine, 2023)
Aortic aneurysms, including abdominal aortic aneurysms (AAAs), is the second most prevalent aortic disease and represents an important cause of death worldwide. AAA is a permanent dilation of the aorta on its infrarenal portion, pathologically associated with oxidative stress, proteolysis, vascular smooth muscle cell loss, immune-inflammation, and extracellular matrix remodeling and degradation. Most epidemiological studies have shown a potential protective role of diabetes mellitus (DM) on the prevalence and incidence of AAA. The effect of DM on AAA might be explained mainly by two factors: hyperglycemia [or other DM-related factors such as insulin resistance (IR)] and/or by the effect of prescribed DM drugs, which may have a direct or indirect effect on the formation and progression of AAAs. However, recent studies further support that the protective role of DM in AAA may be attributable to antidiabetic therapies (i.e: metformin or SGLT-2 inhibitors). This review summarizes current literature on the relationship between DM and the incidence, progression, and rupture of AAAs, and discusses the potential cellular and molecular pathways that may be involved in its vascular effects. Besides, we provide a summary of current antidiabetic therapies which use could be beneficial for AAA.